Effect of Gamma Irradiation on Structural and Optical Properties of Zirconium Incorporated Sodium Borate Glasses. Issue 2 (2nd April 2020) - Roopa,; Eraiah, Bheemaiah
ABSTRACT: The effects of gamma irradiation in the dose rate of 25 kGy on the structural and optical properties of ZrO2 doped sodium borate glasses were studied. Glassy nature confirmed by XRD and all the physical parameters were calculated. IR spectra revealed the characteristic vibrational and stretching bands due to trigonal and tetrahedral borate network. Slight changes were caused by gamma irradiation in the intensities of the characteristic infrared borate bands and zirconium bands. Irradiated samples developed a noticeable absorption band similar to the F-band familiar in alkali halide crystals which clearly indicated that successive irradiation produced defects in the glass material. Substitution of ZrO2 to the glass matrix suppressed the formation of visible absorption band formed by irradiation whereas no extra peak was observed in the spectral regions. A nonlinear trend was ascribed in the energy band gap values due to the creation of more number of non-bridging oxygen atoms. Emission spectra showed five emission bands corresponding to the zirconium ions which decreased to a very low intensity with a red shift after irradiation. Matching the colour co-ordinates bright blue emission was found for 5 mol% ZrO2 in both irradiated and non irradiated sample. GRAPHICAL ABSTRACT: